2022
DOI: 10.2459/jcm.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of systemic inflammatory response syndrome after transcatheter aortic valve implantation

Abstract: AimsSystemic inflammatory response syndrome (SIRS) could affect mortality after transcatheter aortic valve implantation (TAVI) up to 12 months of follow-up. The aim of this study was to evaluate the prevalence of SIRS after TAVI and its impact on all-cause mortality up to 24 months follow-up.MethodsWe retrospectively enrolled 132 patients with symptomatic severe aortic stenosis undergoing TAVI. SIRS development during the first 72 h after the intervention was evaluated. Other postoperative complications were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…24 Atrial fibrillation before and after transcatheter aortic valve implantation Arrotti et al 55 A slightly different analysis was made by Monosilio et al and their evaluation included VARC outcomes, although they focused on postoperatory SIRS which resulted as a predictor of 24-month mortality. 25 Patients with pre-AF had a higher probability of an early bleeding after TAVI than patients in sinus rhythm (OR 17.41, 95% CI 6.49-46.68, P ¼ 0.03). 22 Studies on mortality in patients with preexisting and newonset AF after TAVI showed counteracting results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…24 Atrial fibrillation before and after transcatheter aortic valve implantation Arrotti et al 55 A slightly different analysis was made by Monosilio et al and their evaluation included VARC outcomes, although they focused on postoperatory SIRS which resulted as a predictor of 24-month mortality. 25 Patients with pre-AF had a higher probability of an early bleeding after TAVI than patients in sinus rhythm (OR 17.41, 95% CI 6.49-46.68, P ¼ 0.03). 22 Studies on mortality in patients with preexisting and newonset AF after TAVI showed counteracting results.…”
Section: Discussionmentioning
confidence: 92%
“…A slightly different analysis was made by Monosilio et al and their evaluation included VARC outcomes, although they focused on postoperatory SIRS which resulted as a predictor of 24-month mortality. 25 …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In the last decade, many efforts have been made to improve patient selection for TAVR, and reduce procedural complications and adverse outcomes. [6][7][8][9][10][11][12][13] In patients undergoing TAVR, prosthesis adaptation to the aortic root is of paramount importance to avoid severe paravalvular leaks, achieve an effective orifice area and minimize patientprosthesis mismatch. 14,15 Of interest, it is widely described that TAVR with a balloon-expandable valve was systematically associated with a certain degree of valve stent recoil.…”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter aortic valve replacement (TAVR) is the treatment of choice for patients with severe symptomatic aortic stenosis and has become the preferred strategy in patients at intermediate/high surgical risk 1–5 . In the last decade, many efforts have been made to improve patient selection for TAVR, and reduce procedural complications and adverse outcomes 6–13 . In patients undergoing TAVR, prosthesis adaptation to the aortic root is of paramount importance to avoid severe paravalvular leaks, achieve an effective orifice area and minimize patient–prosthesis mismatch 14,15 …”
Section: Introductionmentioning
confidence: 99%